COVID-19 and optimal lockdown strategies: The effect of new and more virulent strains - Jonathan P. Caulkins; Dieter Grass; Gustav Feichtinger; Richard Hartl; Peter M. Kort; Alexia Prskawetz; Andrea Seidl; Stefan Wrzaczek (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2021)
Most nations have responded to the COVID-19 pandemic by locking down parts of their economies to reduce infectious spread. The optimal timing of the beginning and end of the lockdown, together with its intensity, is determined by the tradeoff between economic losses and improved health outcomes. These choices can be modeled within the framework of an optimal control model that recognizes the nonlinear dynamics of epidemic spread and the increased risks when infection rates surge beyond the healthcare system's capacity. Past work has shown that within such a framework very different strategies may be optimal ranging from short to long and even multiple lockdowns, and small changes in the valuation placed on preventing a premature death may lead to quite different strategies becoming optimal. There even exist parameter constellations for which two or more very different strategies can be optimal. Here we revisit those crucial questions with revised parameters reflecting the greater infectivity of the recently detected "UK variant" of the SARS-CoV-2 virus and describe how the new variant may affect levels of mortality and other outcomes.
Keywords: 330